2020
DOI: 10.1073/pnas.1922159117
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of androgen receptor DNA binding activity through direct interaction with the ETS transcription factor ERG

Abstract: SignificanceProgress in studying the androgen receptor (AR), the primary drug target in prostate cancer, has been hampered by challenges in expressing and purifying active multidomain AR for use in cell-free biochemical reconstitution assays. Here we successfully express full-length and truncated AR variants and demonstrate that the oncogenic ETS protein ERG, responsible for half of all prostate cancers, enhances the ability of AR to bind DNA through direct interaction with AR. In addition to providing a bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 58 publications
4
58
1
Order By: Relevance
“…The androgen receptor (AR) is a key transcription factor that promotes luminal cell fates and AR activity is necessary for the growth of all early stage prostate tumors. Several studies indicate that ERG can cooperate with AR in promoting luminal cell fate [11,12,13]. In contrast to these findings, we and others have shown that expression of ERG in the immortalized-normal prostate cell line RWPE1 does not promote luminal epithelial differentiation, but rather promotes the seemingly opposite phenotypes of migration, invasion, and epithelial to mesenchymal transition (EMT) [14,15,16,17,18].…”
Section: Introductioncontrasting
confidence: 61%
“…The androgen receptor (AR) is a key transcription factor that promotes luminal cell fates and AR activity is necessary for the growth of all early stage prostate tumors. Several studies indicate that ERG can cooperate with AR in promoting luminal cell fate [11,12,13]. In contrast to these findings, we and others have shown that expression of ERG in the immortalized-normal prostate cell line RWPE1 does not promote luminal epithelial differentiation, but rather promotes the seemingly opposite phenotypes of migration, invasion, and epithelial to mesenchymal transition (EMT) [14,15,16,17,18].…”
Section: Introductioncontrasting
confidence: 61%
“…Despite the initial efficacy of ADT, the surviving cells show a persistent and often, an amplified AR signaling axis. Numerous studies have shown that an amplification of ligand-independent AR signaling occurs due to numerous crosstalk between AR and parallel non-AR signaling pathways [17,20,42,[64][65][66] . Therefore, strategies to suppress both AR and non-AR signaling would be needed to ultimately suppress the outgrowth of CRPC cells.…”
Section: Ar Signaling Hormone Deprivation and Crpc Outgrowthmentioning
confidence: 99%
“…In a more recent publication, this group also showed that gene polymorphisms in antioxidant enzymes correlate with the efficacy of ADT, clearly implicating the importance of oxidative stress with CRPC outgrowth [160] . In this respect, ligand-receptor interactions between androgens and AR is a major regulator of redox signaling in PCa cells [66,[161][162][163] and in dictating treatment resistance [162] . Therefore, it is now well accepted that sudden changes in androgen levels, such as during hormone deprivation, can drastically alter cellular homeostasis to increase oxidative stress, ROS production and dysregulated redox signaling networks.…”
Section: Is There a Therapeutic Benefit Of Antioxidants In Crpc Progrmentioning
confidence: 99%
“…We therefore examined the extent to which the findings of AR dependence of genes encoding kinases and phosphatases derived from LNCaP cells can be extrapolated to other AR-positive cell lines, such as VCaP. VCaP cells express the TMPRSS2-ERG gene fusion and show AR gene amplification, which can each impact the composition of the AR cistrome (Waltering et al 2009, Yu et al 2010, Makkonen et al 2011, Wasmuth et al 2020. Analyses of two publically available and independent AR ChIP-Seq data sets derived from VCaP cells (Massie et al 2011, Asangani et al 2014) employing the same selection criteria used on LNCaP cell data (i.e.…”
Section: Transcriptional Control By Ar Over Kinases and Phosphatasesmentioning
confidence: 99%